Solar Water Pump with Four Different Time Slots for Farming Activities - Isham, Ikhsan; Ramli, Khairun Nidzam (Evolution in Electrical and Electronic Engineering, 2024)
This project aims to design a water pump system that runs on solar power and has four different time slots to maximise water utilisation and encourage environmentally friendly farming methods. Farmers face several obstacles since typical water pump systems are unwieldy, noisy, and difficult to operate. The goals of this research are to utilise Arduino to design a solar water pump system that distributes water at four distinct times, to provide an intuitive interface for adjusting the time slot, and to determine the overall power consumption of the system. The methodology involves designing and implementing a control system using Arduino, motor, water pump, and PV solar panel, focusing on four distinct time slots: morning, afternoon, evening, and late evening. Quantitative results from the study indicate that the system consistently delivers reliable performance, providing a steady water flow of 8.5 to 10 liters per minute with a daily power consumption of approximately 72.9W. The system efficiently operates within designated time slots, ensuring optimal water distribution and energy usage. In conclusion, the solar water pump system featuring four distinct time slots exhibits noteworthy advantages concerning energy efficiency, cost-effectiveness, and ecological effects. The initiative promotes sustainable water management, enhances the quality of life in rural communities, and shows the possibility for scalable and flexible renewable energy solutions in agricultural activities. The efficiency and affordability of such systems might be improved with more study and development, opening the door for wider use and promoting a sustainable future.